Integration of Technology in Islamic Education Learning at Al Hadi Islamic Middle School in The Academic Year of 2024/2025 - Amani, Nur Raihanah; Shobahiya, Mahasri (Al Ulya: Jurnal Pendidikan Islam, 2025)
The advancement of technology has brought about changes in many aspects, one of which is education. This provides educational institutions with the opportunity to utilize technology in learning. This research aims to explain the use of technology in Islamic Religious Education learning at Al Hadi Islamic Middle School Mojolaban, Special Program Class for Girls, as well as the benefits and challenges of technology implementation. The research used a qualitative research method with a phenomenological approach. Data was collected directly from the research location and previous journals related to the research subject. Data collection methods included observation, interviews, and documentation. The data obtained was then analyzed using the Miles and Huberman interactive qualitative data analysis technique. The results show that using smart TV facilities in Islamic Religious Education learning makes the learning process more effective and attracts students’ attention to understand the subject. In the utilization of technology in learning, there are several benefits as well as challenges. One of the benefits is that it makes it easier for teachers to deliver the learning material, while the challenge is the teacher's ability to select content that aligns with Islamic teachings.